Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Let's solve each equation one by one to determine whether they have no solution, one solution, or infinitely many solutions.
### Equation 1:
[tex]\[ -1.7v + 2.8 = 1.4v - 3.1v + 2.8 \][/tex]
1. Combine like terms on the right-hand side:
[tex]\[ -1.7v + 2.8 = (1.4v - 3.1v) + 2.8 \][/tex]
[tex]\[ -1.7v + 2.8 = -1.7v + 2.8 \][/tex]
2. Subtract [tex]\(-1.7v + 2.8\)[/tex] from both sides:
[tex]\[ 0 = 0 \][/tex]
This equation simplifies to an identity [tex]\(0 = 0\)[/tex], which means it has infinitely many solutions.
### Equation 2:
[tex]\[ 4a - 3 + 2a = 7a - 2 \][/tex]
1. Combine like terms on the left-hand side:
[tex]\[ (4a + 2a) - 3 = 7a - 2 \][/tex]
[tex]\[ 6a - 3 = 7a - 2 \][/tex]
2. Subtract [tex]\(6a\)[/tex] from both sides:
[tex]\[ -3 = a - 2 \][/tex]
3. Add 2 to both sides:
[tex]\[ -1 = a \][/tex]
This equation has one solution, [tex]\(a = -1\)[/tex].
### Equation 3:
[tex]\[ \frac{1}{5}f - \frac{2}{3} = -\frac{1}{5}f + \frac{2}{3} \][/tex]
1. Combine like terms by adding [tex]\(\frac{1}{5}f\)[/tex] to both sides:
[tex]\[ \frac{1}{5}f + \frac{1}{5}f - \frac{2}{3} = \frac{2}{3} \][/tex]
[tex]\[ \frac{2}{5}f - \frac{-2}{3} = \frac{2}{3} \][/tex]
2. Add [tex]\(\frac{2}{3}\)[/tex] to both sides:
[tex]\[ \frac{2}{5}f = \frac{2}{3} + \frac{2}{3} \][/tex]
[tex]\[ \frac{2}{5} + \frac{2}{6} != \frac{1}{5} \][/tex]
This equation has no solution.
### Equation 4:
[tex]\[ 2y - 3 = 5 + 2(y - 1) \][/tex]
1. Distribute the 2 on the right-hand side:
[tex]\[ 2y - 3 = 5 + 2y - 2 \][/tex]
Combine like terms on the right-hand side:
[tex]\[ 2y - 3 = 2y + 3 \][/tex]
2. Subtract [tex]\(2y\)[/tex] from both sides:
[tex]\[ -3 = 3 \][/tex]
This is a contradiction, so the equation has no solution.
### Equation 5:
[tex]\[ -3(n + 4) + n = -2(n + 6) \][/tex]
1. Distribute the constants:
[tex]\[ -3n - 12 + n = -2n - 12 \][/tex]
2. Combine like terms on both sides:
[tex]\[ -2n - 12 = -2n - 12\][/tex]
Since both sides are equal, this equation has infinitely many solutions.
### Summary:
- Equation 1: Infinitely many solutions
- Equation 2: One solution [tex]\((a = -1)\)[/tex]
- Equation 3: No solution
- Equation 4: No solution
- Equation 5: Infinitely many solutions
### Equation 1:
[tex]\[ -1.7v + 2.8 = 1.4v - 3.1v + 2.8 \][/tex]
1. Combine like terms on the right-hand side:
[tex]\[ -1.7v + 2.8 = (1.4v - 3.1v) + 2.8 \][/tex]
[tex]\[ -1.7v + 2.8 = -1.7v + 2.8 \][/tex]
2. Subtract [tex]\(-1.7v + 2.8\)[/tex] from both sides:
[tex]\[ 0 = 0 \][/tex]
This equation simplifies to an identity [tex]\(0 = 0\)[/tex], which means it has infinitely many solutions.
### Equation 2:
[tex]\[ 4a - 3 + 2a = 7a - 2 \][/tex]
1. Combine like terms on the left-hand side:
[tex]\[ (4a + 2a) - 3 = 7a - 2 \][/tex]
[tex]\[ 6a - 3 = 7a - 2 \][/tex]
2. Subtract [tex]\(6a\)[/tex] from both sides:
[tex]\[ -3 = a - 2 \][/tex]
3. Add 2 to both sides:
[tex]\[ -1 = a \][/tex]
This equation has one solution, [tex]\(a = -1\)[/tex].
### Equation 3:
[tex]\[ \frac{1}{5}f - \frac{2}{3} = -\frac{1}{5}f + \frac{2}{3} \][/tex]
1. Combine like terms by adding [tex]\(\frac{1}{5}f\)[/tex] to both sides:
[tex]\[ \frac{1}{5}f + \frac{1}{5}f - \frac{2}{3} = \frac{2}{3} \][/tex]
[tex]\[ \frac{2}{5}f - \frac{-2}{3} = \frac{2}{3} \][/tex]
2. Add [tex]\(\frac{2}{3}\)[/tex] to both sides:
[tex]\[ \frac{2}{5}f = \frac{2}{3} + \frac{2}{3} \][/tex]
[tex]\[ \frac{2}{5} + \frac{2}{6} != \frac{1}{5} \][/tex]
This equation has no solution.
### Equation 4:
[tex]\[ 2y - 3 = 5 + 2(y - 1) \][/tex]
1. Distribute the 2 on the right-hand side:
[tex]\[ 2y - 3 = 5 + 2y - 2 \][/tex]
Combine like terms on the right-hand side:
[tex]\[ 2y - 3 = 2y + 3 \][/tex]
2. Subtract [tex]\(2y\)[/tex] from both sides:
[tex]\[ -3 = 3 \][/tex]
This is a contradiction, so the equation has no solution.
### Equation 5:
[tex]\[ -3(n + 4) + n = -2(n + 6) \][/tex]
1. Distribute the constants:
[tex]\[ -3n - 12 + n = -2n - 12 \][/tex]
2. Combine like terms on both sides:
[tex]\[ -2n - 12 = -2n - 12\][/tex]
Since both sides are equal, this equation has infinitely many solutions.
### Summary:
- Equation 1: Infinitely many solutions
- Equation 2: One solution [tex]\((a = -1)\)[/tex]
- Equation 3: No solution
- Equation 4: No solution
- Equation 5: Infinitely many solutions
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.